PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 5 DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DI SD LABSCHOOL UNESA 1 SURABAYA - Alfiyah Wulandari; Farida Istianah; Ismawatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve student learning outcomes in the Pancasila education subject in class VC of SD Labschool Unesa 1 Surabaya. The strategy in this consider is Classroom Activity Inquire about which is isolated into two cycles, with stages of arranging, execution of activities, perception, assessment, and reflection. The subjects of the consider were 19 understudies, with subtle elements of 8 male understudies and 11 female understudies. The inquire about rebellious were taken from test information, perception and documentation. Through information preparing, the learning results of understudies in cycle I gotten an normal esteem of 78.4 with learning completeness of 73.68%. The normal esteem in cycle II was 84.2 with learning completeness of 89.47%. The comes about of the gaint test in both cycles appeared an increment in learning results with the "direct" category. So that the application of wordwall media is compelling in making strides understudy learning results.